Systematic identification of regulatory elements in Leukemia. - Komal Tara; Nisar Ahmed Shar; Amna Amin Sethi (International Journal of Endorsing Health Science Research, 2023)
Abstract Background: Leukemia is a type of cancer that originates from the bone marrow's blood-forming stem cells. Cancer cells don't follow the usual cellular differentiation and function pathway, so they supersede the healthy cells. Depending on the population and maturity level of abnormal cells, leukemia can be classified as Acute or Chronic.